Yam (Dioscorea rotundata) tuber waste as feed for poultry production: An alternative kitchen garbage waste management - Nnamdi M. Anigbogu; Amen N. Ononuju; Christopher A. Agida (Syiah Kuala University, 2023)
High cost of feedstuff especially maize and its major contribution of energy source between man and livestock. The study assessed the effect of yam tuber waste meal on broiler bird performance and as an alternative kitchen garbage waste. Specific objectives determined the growth performances, carcass parameters and cost benefits. The experiment lasted for 8 weeks and was conducted at the Poultry Unit of the Teaching and Research Farm, Michael Okpara University of Agriculture Umudike, Abia State, Nigeria. A total of 220day old broiler chicks (mixed sexes) of Agric-tech were selected for the study. The diets consist of Diet 1 = 44% maize and 0% yam tuber waste meal, Diet 2 = 32% maize and 12% yam tuber waste meal, Diet 3 = 22% maize and 22% yam tuber waste meal and Diet 4 = 12% maize and 32% yam tuber waste meal, where palm kernel cake, wheat offal, soybean meal, local fish meal, limestone, vitamin premix, lysine, methionine and salt were used to balance the diets. The feed intake was measured daily, while the weight gain, feed efficiency, efficiency of feed utilization, cost benefits and feed conversion ratio were calculated at the end of the study. The result of the weight gain, the efficiency of feed utilization, feed conversion ratio and average daily weight gain had the same significance level (p0.05) on Diets 3 and 4, respectively, higher than those fed to the other Diets. While the total feed intake and cost benefits analysis showed significance (p0.05) among each other, the average daily feed intake and feed efficiency were not significant (p0.05) among treatments. The dress percentage, dress weight and liveweight were significant (p0.05) across the treatments. Conclusively, using yam tuber waste meal in replacement for maize in broiler diets revealed no adverse effect; and could serve as an alternative for kitchen garbage waste. The study, therefore, recommends that; yam tuber waste meal be included at 22 – 32% in broiler diets without deleterious effects in all parameters studied.